ACL graft selection: state of the art. Issue 3 (10th January 2018) - Koga, Hideyuki; Zaffagnini, Stefano; Getgood, Alan M; Muneta, Takeshi
Abstract : Despite recent developments in anterior cruciate ligament (ACL) reconstruction techniques, there are still several intraoperative factors affecting clinical outcomes that remain widely debated. Among such factors, graft selection might be the most critical yet controversial question for surgeons. As the primary factor influencing a patient's choice for the ACL graft is surgeon recommendation, surgeons have to consider several factors to select the best graft for each patient. Graft options currently include autograft, allograft or synthetic grafts. In terms of autograft, there are three main options: hamstring tendon, bone-patellar tendon-bone (BPTB) and quadriceps tendon, the two most commonly used being hamstring tendon and BPTB. Limited evidence is available to select the one best graft for every individual patient. Graft selection should be based on the reported rate of graft failure/revision and be individualised according to multiple factors such as gender, age, activity level and type of activity, complications and other patient needs and demands. Furthermore, surgeons should be familiar with a variety of grafts, their specific associated surgical procedures and the advantages and disadvantages of each, with the aim of offering the best graft selection for each individual patient.